Optimum KOH wet etching of cantilever tip for better image captured by nanoeducator - Edy Sutjipto, Agus Geter; Faris, Waleed Fekry; Adesta, Erry Yulian Triblas; Hanim, Hafizah (Trans Tech Publications Ltd., Switzerland, 2011)
The development of the various scanning probe microscopy techniques has revolutionized the study of surface structure up to atomic scale. Among these techniques, Nanoeducator as scanning force microscope or SFM has been developed to allow the accomplishment of various measuring techniques both for scanning tunneling microscope (STM) and non-contact atomic force microscope (AFM). However, there is no exact guidance how to fabricate cantilever to gather the good image. In order to achieve the better cantilever for students, this paper emphasizes on tip’s processing by altering etching length parameter as tip plays an important role to achieve better quality image during scanning operation. This paper also provides a guide for undergraduate student to know better about this machine as well as the principle behind it for them to acquire better quality image for their works. It was found that the number of turning of tungsten and etching time could produce good tip of cantilever. It is recommended for lecturers, students and technician to consider about turning and time of etching to produce a better tip of cantilever in Nanoeducator.